Law Number 11/2012 on the Juvenile Criminal Justice System in Overcoming Street Crime "Klitih" in Yogyakarta City - Isnawan, Fuadi (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
Street crime by teenagers in the city of Yogyakarta is evolving in its motives, it is no longer a matter of gangs between schools but has expanded beyond that. The motives also vary, from just a whim to show their strength to the intention to show their strength by hurting other innocent people. The Yogyakarta City Police have taken decisive action, they have made various preventive and repressive efforts to tackle street crime, but it is not enough to minimize the existence of these crimes. This paper will examine the factors that hinder the police from tackling street crimes and how to make teenagers aware of them. This writing is done in an empirical juridical manner to review the two things that are used as topics in this paper. The results obtained include the use of the Juvenile Criminal Justice system which is less able to prevent street crimes committed by adolescents in Yogyakarta City, because it is like a double-edged knife which means that the imposition of punishment must pay attention to the best interests of the child, while what is done has posed a threat and even caused real victims. Things that can be done to overcome can be done intensive counseling in schools about it. The suggestion given to overcome street crime is to be a little firmer in sanctions so that the function of the criminal law itself can protect people and provide a deterrent effect for the perpetrators.